Basic study on dynamic reliability of machinery and piping system supported by elasto-plastic supports - Atsuhiko SHINTANI (The Japan Society of Mechanical Engineers, 2017)
Recently, probabilistic evaluation has been required in the seismic design. In this study, a design method of piping system supported by elasto-plastic damper based on dynamic reliability of pipings was proposed. First, an analytical model of an L-type cantilevered piping system with weight at the top end subjected to seismic input was derived, considering the nonlinear characteristics of the elasto-plastic dampers. Installation of a lead extrusion damper (LED) was assumed as the elasto-plastic damper. The force-displacement relationship of the LED was given by a bilinear hysteretic curve. Seismic input was modeled as white Gaussian noise. The vibration behaviors were calculated for various seismic inputs, and the stress and the energy absorption were calculated. On the basis of the results, the evaluation indices, such as the dynamic reliability, the energy absorption ratio, and the balance of energy absorption, were calculated. Finally, optimization of the support locations was investigated on the basis of the view point of the dynamic reliability. In addition, the effects of the capacities of the two supports on the evaluation index are also investigated. As a result, Jpiping was highest when Node 10 was supported at B. Jenergy was higher when Supports A and B were close to the weight but a little apart from each other. Jbalance was lower when Supports A and B were close to each other. Furthermore, it was obtained that the effect of Support B capacity on the response behavior of pipings is larger than that of Support A capacity.